Analysis of HBsAg Immunocomplexes and cccDNA Activity During and Persisting After NAP‐Based Therapy. Issue 11 (10th July 2021) - Bazinet, Michel; Anderson, Mark; Pântea, Victor; Placinta, Gheorghe; Moscalu, Iurie; Cebotarescu, Valentin; Cojuhari, Lilia; Jimbei, Pavlina; Iarovoi, Liviu; Smesnoi, Valentina; Musteata, Tatina; Jucov, Alina; et al.
Abstract : Therapy with nucleic acid polymers (NAPs), tenofovir disoproxil fumarate (TDF), and pegylated interferon (pegIFN) achieve high rates of HBsAg loss/seroconversion and functional cure in chronic hepatitis B virus (HBV) infection. The role of hepatitis B surface antigen (HBsAg) seroconversion and inactivation of covalently closed circular DNA (cccDNA) in establishing functional cure were examined. Archived serum from the REP 401 study was analyzed using the Abbott ARCHITECT HBsAg NEXT assay (Chicago, IL), Abbott research use–only assays for HBsAg immune complexes (HBsAg ICs), circulating HBV RNA, and the Fujirebio assay for hepatitis B core‐related antigen (HBcrAg; Malvern, PA). HBsAg became < 0.005 IU/mL in 23 participants during NAP exposure, which persisted in all participants with functional cure. HBsAg IC declined during lead‐in TDF monotherapy and correlated with minor declines in HBsAg. Following the addition of NAPs and pegIFN, minor HBsAg IC increases (n = 13) or flares (n = 2) during therapy were not correlated with HBsAg decline, hepatitis B surface antibody (anti‐HBs) titers, or alanine aminotransferase. HBsAg IC universally declined during follow‐up in participants with virologic control or functional cure. Universal declines in HBV RNA and HBcrAg during TDF monotherapy continued with NAP + pegIFN regardless of therapeutic outcome. At the end of therapy, HBV RNA was undetectable in only 5 of 14 participants with functional cure but became undetectable after removal of therapy in all participants with functional cure. Undetectable HBV RNA at the end of therapy in 5 participants was followed by relapse to virologic control or viral rebound. Conclusion: Anti‐HBs‐independent mechanisms contribute to HBsAg clearance during NAP therapy. Inactivation of cccDNA does not predict functional cure following NAP‐based therapy; however, functional cure is accompanied by persistent inactivation of cccDNA. Persistent HBsAg loss with functional cure may also reflect reduction/clearance of integrated HBV DNA. Clinicaltrials.org number NCT02565719. Abstract :